A case study of strategic leadership in the creation and development of a privately owned newspaper in Zambia - Mungonge, Goliath (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
Roles of various constituent elements of Strategic Leadership address deep and continuing issues relating to the creation and development of any organization. What is required to help firms successfully navigate the dynamics and uncertain environment in which they compete today to be successful is addressed. The founding in July 1991 of The Post, a privately owned Zambian newspaper, provided a unique opportunity to investigate the roles that various constituent elements of strategic leadership have played in its success. This is largely because much is already known about how state-owned media are managed, financed, and sustained by the state itself, which is fully involved in their re-capitalization and operating costs. The themes identified are at the heart of current debates about the capacity of private organizations to respond to new expectations, market realities, no state funding, globalization, technology, and a long list of other challenges so as to become market driven enterprises. The case of The Post is seen to present a story of an enduring publication in times of political, financial, social and other adversities and the research participants have no illusions about the success of the publication. The case study of The Post also gives useful insight into the many challenges and obstacles faced by the newspaper. It offers examples of determination, focused courage and innovation, complemented by strategic leadership. This was done by means of what emerged from the insight and experiences of the six research participants that were part of the founders of the newspaper and those associated with the development of the newspaper since its inception.
Keywords: Newspapers -- Zambia; Strategic planning -- Zambia -- Case studies; Mass media -- Zambia -- Case studies; Journalism -- Zambia -- Case studies; Newspaper publishing -- Zambia -- Case studies; Press -- Zambia -- Case studies